Sports Law in Nepal: Reference to Doping in Football - Maharjan, Satya Narayan (Kathmandu School of Law Review, 2022)
Doping is the misuse of certain substances to enhance sporting performance, however; there are lots of side effects to the health of the athlete and others associated with sports. Having a direct impact on fair competition of sports, various Anti-doping laws are being framed at both the National and International levels to preserve the integrity of sport. In a developing country like Nepal, this issue of doping is not very familiar in football but concerned bodies like ANFA, and NSC are making efforts to combat the problem by organizing awareness programs and medical tests before games. It is the authorities’ responsibility to be aware of these sports crimes and to ensure their prevention to facilitate fair competition. This research paper aimed to apply the empirical research method for doping analysis and focus on the problem of doping, its impact, the actual application of doping whether it is appropriate or not, Nepalese laws dealing with doping, case laws, and international standards on doping and obligations of State as well.